Avaliação da atividade biológica em diferentes manejos de áreas de várzea para implantação da cultura da soja. - Cristofari, Lisiele Pozzatto (2022)
Soybean crop has become an important tool for managing crop rotation with irrigated rice in floodplain areas. However, there are obstacles to the establishment and uniformity of soybean production depending on the characteristics of the soil and the environment. The present work aimed to identify a soil management proposed in the off-season to analyze their influence on the physical and biological conditions of the soil in order to provide better conditions for the establishment and productivity of the soybean crop in the subsequent harvest. The experiment was conducted in the district of Arroio Grande, in the municipality of Santa Maria-RS in the 2020/2021 crop, in an area with irrigated rice cultivation in the 2019/2020 crop. The treatments were composed of off-season management through a fallow area (there was no soil management), soil subsoiling and soil subsoiling followed by a vegetation cover. From these managements, the biological quality of the soil was evaluated through the evaluation of the enzymatic activity established between the microorganisms of the soil and the soybean, being analyzed the Glomalin, Acid Phosphatase, Arylsulfatase, β-glucosidase and the activity of the mycorrhizal fungi (Mycorrhization), in addition to the yield components of the crop. The collections were carried out in 25 points of each treatment, and each sample had 500g of soil and root, where in the laboratory they were sieved in 2 mm sieves and stored under refrigeration (4°C) for the analysis. From the results obtained in the experiment, it was verified that the soil management (subsoiling and subsoiling + cover) carried out in the off season influences the microbial activity of the soil and its symbiosis with soybean, providing greater crop productivity. The results of mycorrhization of soybean roots were evaluated using Pearson's correlation. Great influence was observed on the enzymes Glomalin, Acid Phosphatase, Arylsulfatase, β-glycosidase for soybean cultivation. As each enzyme has specific characteristics and functions, it can be inferred that acid phosphatase was related to soybean productivity when fallow management was carried out in the off-season. The enzymes β-Glycosidase and Arylsulfatase and the protein Glomalin interacted with PMG (weight of a thousand grains) in the management of subsoiling with vegetal cover and Mycorrhization was linked to the number of legumes and number of nodes per soybean plant in the management of subsoiling carried out. in the off season.